Management of waterlogged saline soils and strategies to minimize problems of drainage effluent disposal - Gupta, S. K., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Expansion of irrigation to arid and semi-arid regions through inter basin transfer of water together with research and development in agriculture were instrumental to tide over the food scarcity crisis in the country. The expansion based on inter basin transfer of water, however, led to adverse environmental impacts. Within 10-15 years of operation of the projects, conditions of waterlogging and soil salinization appeared in many irrigation projects. The present paper highlights the causes of waterlogging and soil salinity in irrigation commands with reference to the projects in the Gujarat and Karnataka States of India. Amongst the various factors, inadequate drainage ranks as number one cause for the development of waterlogging in the commands. In the monsoon climatic conditions as prevails in India, surface drainage seems to be essential although it may not be able to control the water table. The paper also deals with the attempts being made in various irrigation commands to establish the feasibility of subsurface drainage for the reclamation and management of waterlogged salt affected soils. Some of the major findings are discussed to show that drainage cost in monsoon climatic conditions could be substantially reduced over the conventional designs applicable to humid climatic regions. In recent years, it has been seen that drainage effluent disposal could be a serious issue in planning drainage programs. Present paper highlights the water quality issues in India under various kinds of drainage systems. Drainage design issues (depth, spacing and bi-level drainage) and operational schedules that help to minimize generation of drainage effluent have been discussed. Direct and conjunctive use strategies have been highlighted to show that reuse of poor quality drainage effluent near to the generation sites is feasible. Mathematical models have been used to show that such a strategy would be sustainable on a long term basis.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.